Johanson-Blizzard Syndrome with Short Stature - Khorasani, Enayatollah Nemat; Mansouri, Fariba (Journal of Nepal Paediatric Society, 2016)
Johanson–Blizzard syndrome (JBS) is a rare, sometimes fatal autosomal recessive multisystem congenital disorder featuring abnormal development of the pancreas, nose and scalp, with mental retardation, hearing loss and growth failure. It is sometimes described as a form of ectodermal dysplasia. The disorder is especially noted for causing profound developmental errors and exocrine dysfunction of the pancreas, and it is considered to be an inherited pancreatic disease. We report a ten years Irannian child with signs and symptoms suggestive of this syndrome (JBS). J Nepal Paediatr Soc 2015;35(3):287-289.